1 ( 4 0 ) + 3 ( 3 8 ) + 5 ( 3 6 ) + … + 3 7 ( 4 ) + 3 9 ( 2 ) = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice work as usual. I love the addition of colours in your work. Note: Try replacing b n with a n for equation number two, else you would have a n = 2 n − 1 = 4 2 − 2 n .
Despite a good conventional approach, can you think of a simpler solution? Hint: 1 + 4 0 = 3 + 3 8 = 5 + 3 6 = … = 3 9 + 2 .
Double the expression:
= = = 1 ( 4 0 ) + 2 ( 3 9 ) + 3 ( 3 8 ) + 4 ( 3 7 ) + … + 3 9 ( 2 ) + 4 0 ( 1 ) n = 1 ∑ 4 0 n ( 4 1 − n ) 4 1 n = 1 ∑ 4 0 n − n = 1 ∑ 4 0 n 2 4 1 ⋅ 2 4 0 ⋅ 4 1 − 6 4 0 ( 4 1 ) ( 2 ⋅ 4 0 + 1 ) = 1 1 4 8 0
Divide the expression back by two: 1 1 4 8 0 ÷ 2 = 5 7 4 0 .
Problem Loading...
Note Loading...
Set Loading...
From sequence 1 , 3 , 5 , … , 3 9 → 2 ( 1 ) − 1 , 2 ( 2 ) − 1 , 2 ( 3 ) − 1 , … , 2 ( 2 0 ) − 1
Thus, a n = 2 n − 1 ⇒ ( 1 )
From sequence 4 0 , 3 8 , 3 6 , … , 2 → 4 2 − 2 ( 1 ) , 4 2 − 2 ( 2 ) , 4 2 − 2 ( 3 ) , … , 4 2 − 2 ( 2 0 )
Thus, a n = 4 2 − 2 n ⇒ ( 2 )
so the both sequences have 20 terms.
From ( 1 ) and ( 2 ) that is
1 ( 4 0 ) + 3 ( 3 8 ) + 5 ( 3 6 ) + … + 3 7 ( 4 ) + 3 9 ( 2 )
= = = = = = = n = 1 ∑ 2 0 ( 2 n − 1 ) ( 4 2 − 2 n ) n = 1 ∑ 2 0 ( − 4 n 2 + 8 6 n − 4 2 ) − 4 n = 1 ∑ 2 0 n 2 + 8 6 n = 1 ∑ 2 0 n − n = 1 ∑ 2 0 4 2 − 4 ( 6 ( 2 0 ) ( 2 0 + 1 ) ( 2 ( 2 0 ) + 1 ) ) + 8 6 ( 2 2 0 ( 2 0 + 1 ) ) − 4 2 ( 2 0 ) − 4 ( 6 ( 2 0 ) ( 2 1 ) ( 4 1 ) ) + 8 6 ( 2 2 0 ( 2 1 ) ) − 8 4 0 − 4 ( 2 8 7 0 ) + 8 6 ( 2 1 0 ) − 8 4 0 − 1 1 4 8 0 + 1 8 0 6 0 − 8 4 0 = 5 7 4 0